Earnings management and post-split drift - Chan, Konan; Li, Fengfei; Lin, Tse-Chun (Journal of Banking & Finance, 2019)
This paper explores whether firms manage their earnings after stock splits to meet the raised expectations from the market due to the positive signal sent by the splits. We first document that post-split drift mainly exists in the first three months and is positively associated with post-split standardized unexpected earnings (SUE). However, the higher post-split SUE of split firms is associated with higher discretionary accruals and abnormally lower R&D expenses. This result is consistent with our hypothesis that split firms overstate their post-split earnings by manipulating accruals and reducing R&D spending. Moreover, post-split abnormal returns increase with discretionary accruals and R&D reduction for about six months and tend to reverse over longer horizons, especially for firms with negative pre-split SUE. Overall, our results indicate that the post-split drift is a short-term phenomenon and partly attributable to the earnings management after the splits.